Balance Within and Across Domains: The Performance Implications of Exploration and Exploitation in Alliances - Lavie, Dovev; Kang, Jingoo; Rosenkopf, Lori (Organization Science, 2011)
Organizational research advocates that firms balance exploration and exploitation, yet it acknowledges inherent challenges in reconciling these opposing activities. To overcome these challenges, such research suggests that firms establish organizational separation between exploring and exploiting units or engage in temporal separation whereby they oscillate between exploration and exploitation over time. Nevertheless, these approaches entail resource allocation trade-offs and conflicting organizational routines, which may undermine organizational performance as firms seek to balance exploration and exploitation within a discrete field of organizational activity (i.e., domain). We posit that firms can overcome such impediments and enhance their performance if they explore in one domain while exploiting in another. Studying the alliance portfolios of software firms, we demonstrate that firms do not typically benefit from balancing exploration and exploitation within the function domain (technology versus marketing and production alliances) and structure domain (new versus prior partners). Nevertheless, firms that balance exploration and exploitation across these domains by engaging in research and development alliances while collaborating with their prior partners, or alternatively, by forming marketing and production alliances while seeking new partners, gain in profits and market value. Moreover, we reveal that increases in firm size that exacerbate resource allocation trade-offs and routine rigidity reinforce the benefits of balance across domains and the costs of balance within domains. Our domain separation approach offers new insights into how firms can benefit from balancing exploration and exploitation. What matters is not simply whether firms balance exploration and exploitation in their alliance formation decisions but the means by which they achieve such balance.